Development of Coordination Abilities of Young Skater 7-8 Years - Fedorova Svetlana Vyacheslavovna (Zien Journals, 2022)
The presented article deals with the development of coordination abilities of young figure skaters aged 7-8.
Keywords: coordination abilities; initial training; figure skating